The Effect of Motivation and Work Environment on Employee Performance at Resort Hotel - I Gede Andika Harianto; Ni Luh Ketut Sri Sulistyawati; Irene Hanna H Sihombing (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2025)
Purpose of the study: This study examines how work environment and motivation jointly influence staff performance at Prama Sanur Beach Hotel in Bali. Design/methodology: A total of 64 employees were selected using non-probability sampling. Primary data were collected through self-administered questionnaires. Data were analyzed using multiple linear regression in SPSS version 23 for Windows. Findings: Results show that motivation (X1) has a significant and positive partial effect on employee performance. The work environment (X2) also exerts a significant and positive partial effect on performance. Together, motivation and work environment significantly influence employee performance. The model’s coefficient of determination (R²) is 71.4%, indicating that a substantial proportion of the variance in performance is explained by these two independent variables. Research limitations/Implications: Theoretically, it confirms that work environment and motivation are key, interacting predictors of employee performance, supporting integrated performance models in hospitality and tourism research. Practically, it suggests that hotel managers can substantially improve staff performance by simultaneously enhancing physical and psychosocial work conditions and implementing motivation-focused HR practices such as recognition, development opportunities, and participative management. Methodologically, the findings provide a replicable regression-based approach for mid-sized hotel studies while highlighting the need for future research to adopt more comprehensive structural models, include additional variables (e.g., leadership, compensation, work stress), and use larger, more diverse, multi-site samples to strengthen generalizability. Novelty/Originality of the study: This study provides context-specific evidence on the combined influence of work environment and motivation on employee performance within a luxury beach hotel in Bali, offering practical insights for hospitality management in similar resort settings.